PENCEGAHAN DAN PEMBERANTASAN PRAKTIK MAFIA TANAH MELALUI PENGOPTIMALAN PERAN SATGAS ANTI-MAFIA TANAH - Sinaga, Haposan Sahala Raja (HUKMY : Jurnal Hukum, 2024)
During 2018 to 2022, the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency ('ATR/BPN') recorded handling 305 land cases involving the land mafia. The efforts made by the Ministry of ATR/BPN to eradicate parties involved in land mafia practices are by establishing a Anti-Mafia Land Task Force conducting this research with the aim of legally analyzing the legal position of Task Force and provide recommendations for optimizing the role of Task Force in efforts to prevent and eradicate land mafia practices in Indonesia. This research is juridical-normative research, with a statutory and literature approach. The results of this research: 1) the position of the Anti-Mafia Land Task Force based on its position is at 2 (two) different levels, the ministry level which is appointed and determined based on the decision of the Minister of ATR/BPN and the regional office level. Its role is only to research and analyze land mafia practices and then delegate them to the Police. 2) Optimizing the role of Task Force is carried out with the urgency of establishing the ATR/BPN Ministerial Regulation on Prevention and Eradication of Land Mafia Practices; and changing the form of the Anti-Mafia Land Task Force under the responsibility of the President in accordance with the Presidential Instruction and coordinated by the Coordinating Minister for Political, Legal and Security Affairs involving experts and independent figures.